Taking Offense - Korte, Anne-Marie,Kruse, Christiane,Meyer, Birgit (Wilhelm Fink, 2018)
Preliminary Material /Anne-Marie Korte – Preface /Christiane Kruse , Birgit Meyer and Anne-Marie Korte – Introduction /Birgit Meyer , Christ Iane Kruse and Anne-Marie Korte – Offending Pictures. What Makes Images Powerful /Christiane Kruse – Art and Religion in a Post-Secular, Multi-Religious Society /Nika Spalinger – The Downfall of the Utopias. Pier Paolo Pasolini’s Modernist Heresies /Norbert M. Schmitz – Blasphemous Feminist Art. Incarnate Politics of Identity from a Post-Secular Perspective /Anne-Marie Korte – The Kaaba of New York /Simon O’Meara – From the »Religious« to the »Aesthetic« Image, or the Struggle over Art that Offends /Monica Juneja – Destroying Krishna Imagery. What are the Limits of Academic and Artistic Freedom? /Maruška Svašek – Blood, Sweat and Tears. The Martyred Body in Chinese Performance Art /Tania Becker – Dirty Pictures. Vulgar Street Art in Lahore, Pakistan /Jürgen Wasim Frembgen and Asif Jehangir – A Brief Anatomy of Offensive Imagery /Jojada Verrips – Is There such a Thing as an »Offensive Picture«? /Christoph Baumgartner – The Dynamics of Taking Offense. Concluding Thoughts and Outlook /Birgit Meyer – Biographies /Anne-Marie Korte – List of Illustrations/Image Quotations /Anne-Marie Korte – Taking Offense Religion, Art, and Visual Culture in Plural Configurations /Anne-Marie Korte. What makes an image offensive? — This question is addressed in this volume. It explores tensions and debates about offensive images and performative practices in various settings in and beyond Europe. Its basic premise is that a deeper understanding of what is at stake in these tensions and debates calls for a multidisciplinary conversation. The authors focus on images that appear to trigger strongly negative reactions; images that are perceived as insulting or offensive; those subject to taboos and restrictions; or those that are condemned as blasphemous. In light of recurrent acts of violence leveled against images and symbols in the contemporary, globally entangled world, addressing instances of “icono-clash” (Bruno Latour) from a new post-secular, global perspective has become a matter of urgency
10.30965/9783846763452
Keywords: Religion and culture; Blasphemy; Religious pluralism